Hubungan komunikasi terapeutik perawat pada fase kerja dengan kepuasan pasien terapi intravena di ruangan interna wanita rsud dr. M. Haulussy ambon - Nenny Parinussa; Agnesia M Tandiola (MOLUCCAS HEALTH JOURNAL, 2019)
Therapeutic communication is communication carried out by nurses, especially during the work phase, which takes place in a consciously planned manner with the aim and activities focused on healing patients. New patients will feel satisfied if the health service performance obtained is equal to or exceeds what is expected. This study aims to determine the relationship between therapeutic communication of nurses in the work phase with the satisfaction of intravenous therapy patients in the internal room of the female hospital at dr. M. Haulussy Ambon. The research design used was cross sectional, a study in which data collection of independent and bound variables was carried out at the same time. The number of samples in this study were 50 respondents. The results were tested using a Chi-square test with a significance level of α = 0.05 and it was found that (p value = 0.000) there was a therapeutic relationship between nurses in the work phase and the satisfaction of intravenous therapy patients in the female internal room of RSUD dr. M. Haulussy Ambon (p value = 0,000 <0.05). Suggestions for this study for nurses can communicate therapeutically during the work phase takes place with the purpose and activities focused on healing patients and increasing patient satisfaction, for this study is expected to improve and increase the knowledge of researchers and can be developed for further research on Standard Operating Procedure (SOP) which contains therapeutic communication especially in the work phase.Keywords: Therapeutic communication nurse, patient satisfaction, intravenous therapy.